The effect of surface reconstruction on the oxygen reduction reaction properties of LaMnO3 - Ignatans,R; Mallia,G; Ahmad,EA; Spillane,L; Stoerzinger,KA; Shao-Horn,Y; Harrison,NM; Tileli,V (The Journal of Physical Chemistry C: Energy Conversion and Storage, Optical and Electronic Devices, Interfaces, Nanomaterials, and Hard Matter, 2019)
Perovskites have been widely studied for electrocatalysis due to the exceptional activity they exhibit for surface-mediated redox reactions. To date, descriptors based on density functional theory calculations or experimental measurements have assumed a bulk-like configuration for the surfaces of these oxides. Herein, we probed an initial exposed surface and the screened subsurface of LaMnO3 particles, demonstrating that their augmented activity toward the oxygen reduction reaction (ORR) can be related to a spontaneous surface reconstruction. Our approach involves high energy resolution electron energy loss spectroscopy for the fine structure probing of oxygen and manganese ionization edges under electron beam conditions that leave the structure unaffected. Atomic multiplet and density functional theory calculations were used to compute the theoretical energy loss spectra for comparison to the experimental data, allowing to quantitatively demonstrate that the particle surface layers are La-deficient. This deficiency is linked to equivalent tetrahedral Mn2+ sites at the reconstructed surface, leading to the coexistence of +3 and +2 oxidation states of Mn at the surface layers. This electronic and structural configuration of the as-synthesized particles is indirectly linked to strong adsorption pathways that promote the ORR on LaMnO3, and thus, it could prove to be a valuable design feature in the engineering of catalytic surfaces.